Integrating COBIT and COSO Frameworks for Fraud-Resistant Banking Information Systems: A Unified Model for Enhanced Audit Reliability (gjstudies, 2020)
This research develops and validates an integrated framework combining COBIT(Control Objectives for Information and Related Technologies) for IT governanceand COSO (Committee of Sponsoring Organizations) for internal control to createfraud-resistant banking information systems. Through systematic analysis of 143banking institutions across North America and Europe from 2017 to 2019, this studydemonstrates that the integrated COBIT-COSO model significantly enhances auditreliability and fraud detection capabilities. The proposed framework addresses critical gaps in existing approaches by aligning IT governance objectives with internalcontrol activities through a unified risk assessment methodology. Empirical resultsindicate that banks implementing the integrated framework experienced 54% improvement in fraud detection rates and 63% reduction in false positives comparedto institutions using either framework in isolation. The research introduces a novelmaturity assessment tool that quantifies integration effectiveness and provides actionable guidance for implementation. Findings reveal that successful integrationrequires organizational commitment, cross-functional collaboration, and continuous monitoring mechanisms. This study contributes to both academic literatureand practical implementations by providing evidence-based insights for enhancingbanking information system resilience against evolving fraud threats.